The Effect Of Using Animation On Developing Speaking Skill In Arabic Language Subject - Amanee Abdul Hai; Azlan Bin Shaiful Baharum (AL-QIYAM Centre for Scientific Research and Studies, 2024)
Speaking skills is a part of important element that highly considered in learning Arabic language at University Technology MARA (UiTM). It encourages students to practice speaking Arabic daily both in classroom and outside. Based on pre observations, there are many students who are unable to speak or communicate in Arabic, decreasing performance in speaking test, and medium being used is not attractive. Based on this situation, the author conducted research using animation to improve speaking skills among students. The implementation of animation as a teaching tool in learning Arabic language is indeed an innovation to create an environment that will promote student’s interest. This study discusses the effectiveness of the use animation in improving students’ speaking skill. This study involves 132 students from University Technology MARA (UiTM). The instruments used in this study are pre-test and post-test, observations, and surveys. The results of this study show that the using of animation in learning process is very effective in improving the language proficiency particularly speaking skills.